2019
DOI: 10.3390/app9020218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spray Deposition, Control Efficacy on Wheat Aphids and Working Efficiency in the Wheat Field of the Unmanned Aerial Vehicle with Boom Sprayer and Two Conventional Knapsack Sprayers

Abstract: As a new low volume application technology, unmanned aerial vehicle (UAV) application is developing quickly in China. The aim of this study was to compare the droplet deposition, control efficacy and working efficiency of a six-rotor UAV with a self-propelled boom sprayer and two conventional knapsack sprayers on the wheat crop. The total deposition of UAV and other sprayers were not statistically significant, but significantly lower for run-off. The deposition uniformity and droplets penetrability of the UAV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 39 publications
5
67
0
1
Order By: Relevance
“…showed that the spray method has a significantly effect on pesticide depositions and losses . Sprayer nozzles are also regarded as the key factor affecting droplet deposition and the biological efficacy of pesticide application . For this reason, we also investigated the effect of three different nozzle sizes under differing spray pressures on the droplet distribution of each pesticide.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…showed that the spray method has a significantly effect on pesticide depositions and losses . Sprayer nozzles are also regarded as the key factor affecting droplet deposition and the biological efficacy of pesticide application . For this reason, we also investigated the effect of three different nozzle sizes under differing spray pressures on the droplet distribution of each pesticide.…”
Section: Resultsmentioning
confidence: 99%
“…37 Sprayer nozzles are also regarded as the key factor affecting droplet deposition and the biological efficacy of pesticide application. 17 For this reason, we also investigated the effect of three different nozzle sizes under differing spray pressures on the droplet distribution of each pesticide. The findings revealed that the volume average diameter (VAD) of droplets was proportional to the quantity of the nozzle sizes, with a negative relationship between spray pressure and VAD (Fig.…”
Section: Analysis Of Spraying Deposition and Losses To Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, UAVs have been widely used for spraying pesticides to control pests and diseases. The advantages of aerial application of pesticides by UAVs is substantial, such as high working efficiency, no harmful mechanical damage to crops and soil, low water consumption, reduced pesticide poisoning, high pesticide utilization and high flexibility [8][9][10][11][12][13][14][15][16][17] . Global positioning system (GPS), geographic information system (GIS), BeiDou navigation satellite system (BDS) and real-time kinematic (RTK) automatic navigation technology have been used in the flight control system for precision spraying by UAVs.…”
Section: Introductionmentioning
confidence: 99%